COMBINATION OF FOOT HYDROTHERAPY AND SLOW DEEP BREATHING ON BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Ramadhani, Dwi Yuniar; Mahundingan, Rosari Oktaviana; Ramadhani, Nurlita Arinda Rini; Ramadhani, Irma Yunita; Ramadhani, Berliani Ananda Risvy (jfpublisher, 2023)
Introduction. Hypertension becomes very dangerous when the patient cannot control blood pressure, because it will cause complications. One of the nonpharmacological therapies that can be done is foot hydrotherapy using warm red ginger decoction and slow deep breathing. The purpose of this study was to determine the effect of the combination of red ginger foot hydrotherapy and slow deep breathing on blood pressure in patients with hypertension. Method. Pre-experimental research design with one group pre-test post-test design approach with a sample of 20 people. Total sampling technique. Observation sheet measuring instrument and sphygmomanometer with Wilcoxon statistical test. Result & Analysis. The results of the study obtained blood pressure values before the intervention and found that all respondents had blood pressure in the category of hypertension stage 2 (100%) and after the intervention found 55% in the elevated category and stage 1 hypertension as much as 45%. The results of the static test p-value = 0.000, which shows the effect of the Red Ginger Foot Hydrotherapy combination of Slow Deep Breathing on the blood pressure of hypertensive patients. Discussion. Doing red ginger foot hydrotherapy in combination with slow deep breathing can control blood pressure, but must be supported to consume drugs regularly, exercise, carrying out a diet, and avoiding stress.